Pengaruh Motivasi dan Gaji Terhadap Loyalitas Karyawan “Studi Kasus: PT. Nusantara” - Yap, Farina Jessen (JOURNAL ECONOMICS AND STRATEGY, 2025)
This study aims to see the effect of motivation and salary on employee loyalty at PT Nusantara. This study uses multiple linear regression analysis method to determine the relationship of each independent variable to the dependent variable. The population in this study were all employees at the company totaling 79 people. The sample was taken using a saturated sampling technique where all members of the population were used as samples. Thus, the sample in this study amounted to 79 people. The results of the simultaneous hypothesis test showed that simultaneously motivation and salary had an effect on employee loyalty at PT. Nusantara. Partially, each variable of motivation and salary had an effect on employee loyalty at PT. Nusantara.